Analyzing standardization needs for applying agent technology in industrial environments - Leitão, Paulo (2018)
Multi-agent systems can play an important role in the realization of cyber-physical systems by providing intelligence, flexibility, robustness, self-adaptation, and self-organization to them. In spite of the promising perspective offered and concretized by the deployment of multi-agent systems in a few industrial systems and in several laboratory applications, its industrial adoption is far from the expected widely usage. Beside other issues, standardization is being identified as a critical aspect for this status and requires the need to be compliant with existing industrial practices but also a special effort to influence the specifications of existing standards and/or the introduction of new ones. The main objective of this paper is to analyze necessary standardization needs for applying and deploying agent-based technology in industrial environments, addressing industrial requirements imposed by different application fields.